Exopolysaccharide producing Lactobacillus plantarum SKT109 as adjunct culture in Cheddar cheese production. (November 2018) - Wang, Ji; Fang, Xiaobin; Wu, Tong; Min, Weihong; Yang, Zhennai
Abstract: In vitro antioxidant activity of an exopolysaccharide from Lactobacillus plantarum SKT109 (L-EPS) and potential application of this strain for Cheddar cheese production were evaluated. Cheddar cheese was manufactured using a cheese starter culture consisting of lactococci combined with L. plantarum SKT109 as an adjunct culture. The chemical composition, microbial changes, proteolysis, textural profiles and volatile compounds of the cheeses were studied during 12 weeks of ripening. The experimental cheese made with L. plantarum SKT109 as an adjunct had greater moisture contents than those of the control cheese made with starter alone. L. plantarum SKT109 survived well in Cheddar cheese, with counts of 7.89 log cfu/g at the end of the ripening period. Inclusion of the adjunct strain had no detectable negative effects on cheeses in terms of proteolysis and texture. L. plantarum SKT109 improved the Cheddar cheese flavor profile by increasing the levels of low threshold value compounds including ethyl acetate, 3-methyl-1-butanol, 3-hydroxy-2-butanone and butanone. L-EPS had the strongest scavenging activity toward hydroxyl (68.52%) radicals at a dose of 5 mg/mL. These results indicated that EPS-producing L. plantarum SKT109 or its EPS may be promising ingredients, with favorable effects on cheese texture and flavor as well as potential health benefits. Highlights: L. plantarum SKT109 EPS has strong hydroxyl radicals scavenging activity. L. plantarum SKT109 survived well in Cheddar cheese. L. plantarum SKT109 has no negative effects on cheese proteolysis and texture. L. plantarum SKT109 could improve the Cheddar cheese final flavor profile.